' … as good and ffyne silver as any plate of London towche': Goldsmiths and the market for silver in seventeenth-century Dublin. Issue 2 (4th May 2018) - Cunningham, Jessica
ABSTRACT: Who instigated the development of the production of silverwares in seventeenth-century Dublin: the city's goldsmiths or their consumers? This paper presents the burgeoning market for silver among consumers in early-seventeenth century Ireland as an essential socio-economic condition for encouraging the concerted development of the craft at this time. The paper will also show how the formation by the Dublin guild of goldsmiths of the Company of Goldsmiths of Dublin in 1637 and, with it, the timely regulation of their craft, brought immigrant craftsmen to the capital, cultivating an environment in which the quality of silver produced was regarded to be 'as good and ffyne as any plate of London towche'. A consumer society was well-established in seventeenth-century Ireland and the period witnessed the growing appetite for imported and domestically-manufactured luxury wares among the country's elite. This is particularly apparent with the evidence relating to the consumption of silver; seventeenth-century Irish consumers sourced their domestic silverwares from local and international goldsmiths alike. As the century progressed, the increasing volume of silver produced and acquired in Ireland by Irish consumers was mirrored by the exponentially expanding numbers of goldsmiths operating in Dublin and in other regional centres. Balancing case-study evidence relating to individual goldsmiths and their patrons with quantitative analysis demonstrating the craft's growth and expansion, this paper examines the multiple and complementary factors informing the production of silver in early-modern Ireland.